Functional Outcomes of Dorsal Bridge Plating for Lisfranc Injuries With Routine Implant Retention: A Major Trauma Center Experience. Issue 1 (January 2023) - Onochie, Elliot; Bua, Nelson; Mmerem, Kingsley; Heidari, Nima; Vris, Alexandros; Malagelada, Francesc; Parker, Lee; Jeyaseelan, Luckshmana
Abstract : Objectives: To assess medium-term functional outcomes and the complication profile for unstable Lisfranc injuries treated with dorsal bridge plate (DBP) fixation when implants are not routinely removed. Design: Large single-center retrospective case series. Setting: Level-1 Trauma Center, London, United Kingdom. Patients: Consecutive cases of skeletally mature individuals with unstable Lisfranc injuries treated operatively between 2014 and 2019. Intervention: Open reduction and DBP fixation with implants not routinely removed. Main Outcome Measurements: Patient-reported outcome measures at final follow-up. The Manchester-Oxford Foot Questionnaire summary index was the primary outcome measure. The American Orthopaedic Foot and Ankle Society (AOFAS) midfoot scale, complications, and all-cause reoperation rates were secondary outcome measures. Logistic regression models were used to identify risk factors that influenced outcomes. Results: Eighty-five patients were included. Mean follow-up was 40.8 months (24–72). The mean Manchester-Oxford Foot Questionnaire Summary Index was 27.0 (SD 7.1) and mean AOFAS score 72.6 (SD 11.6). The presence of an intra-articular fracture was associated with poorer outcomes, with worse MOXFQ and AOFAS scores (both P < 0.001). Eighteen patients (21%) required implants removal, with this more likely in female patients (OR 3.89, 95% confidence interval, 1.27 to 12.0, P = 0.02). Eight patients (9%) required secondary arthrodesis. Conclusions: This is the largest series of Lisfranc injuries treated with DBP fixation reported to-date and the only to routinely retain implants. Medium-term outcomes are comparable to existing literature in which implants are routinely removed. The presence of an intra-articular fracture is a poor prognostic indicator. Implant removal is more likely to be needed in female patients. Level of Evidence: Therapeutic Level IV. See Instructions for authors for a complete description of levels of evidence.